Cross-modal repetition effects in the mu rhythm indicate tactile mirroring during action observation. (February 2015) - Coll, Michel-Pierre; Bird, Geoffrey; Catmur, Caroline; Press, Clare
Abstract: Similar cortical activations during the experience and observation of touch suggest the presence of a tactile mirroring system. However, the specificity of observation-related activity – i.e., whether observation excites the same representations as experience of that specific tactile stimulation – is still to be established. Furthermore, central mu rhythms are attenuated during the experience and observation of touch, and also during action observation and execution, making it unclear whether they index processing of predominantly tactile or motor features of observed actions. The present study used an electroencephalography (EEG) cross-modal repetition paradigm to assess the relative tactile and motor specificity of mu attenuation during action observation. Two experiments were carried out during which participants executed and observed actions in alternation, and the repetition of either tactile or motor features of the actions were manipulated. The mu signal over central electrodes varied as a function of tactile repetition, consistent with the claim of a tactile mirroring system and its reflection in the mu signal. Of note was the fact that mu attenuation was sensitive only to manipulation of tactile – not motor – properties of actions, suggesting that caution should be employed when interpreting mu effects during action observation as reflective of motor mirroring.